Evaluación de ensayos clonales de Hieronyma Alchorneoides, en la zona norte de Costa Rica - Alvarado-Cerdas, Diego Alberto (Instituto Tecnológico de Costa Rica, 2016)
Pilón (Hieronyma alchorneoides) is one of the native species that presents greater adaptation to plantations (Delgado, Marcelino, Murillo & Castillo, 2003), due to its growth characteristics, multiple uses, high ecological value, is a strategic native species of the country (Piotto, 2001; Chowdhury & Chang, 2005; Gause, 2005). The vegetative propagation becomes an efficient method of reproduction of the pylon given its limitations for its sexual reproduction; Due to the difficulties in locating seed sources, the sex of the tree is not clearly differentiated, fruit production is very variable over time and among trees, being recalcitrant seeds, their germination capacity is lost in a few days After harvest (Abdelnour, Aguilar & Valverde, 2011). This paper evaluated the growth in diameter, commercial value and commercial volume of 2 clonal tests of Hieronyma alchorneoides, established in September 2012 in the northern zone of Costa Rica, with the objective of certifying the first seed source in Costa Rica. We reject the null hypothesis and accept the alternative hypothesis that establishes the existence of significant differences among the evaluated genotypes. The genetic values show an elite population conformed by the 10 best clones, whose use will generate a genetic gain of 3.2% in diameter that means a potential reduction of 0.7 years in the cultivation of this species. The environmental genotype interaction is low (c2int ≤ 0.01), so the clonal collection of “pilón” presents a similar growth behavior in the northern zone of Costa Rica.
Proyecto de Graduación (Licenciatura en Ingeniería Forestal) Instituto Tecnológico de Costa Rica. Escuela de Ingeniería Forestal, 2016.
Keywords: Ensayo clonal; Mejoramiento genético; Silvicultura; Especies nativas; Reforestación; Research Subject Categories::FORESTRY, AGRICULTURAL SCIENCES and LANDSCAPE PLANNING::Plant production::Forestry